INFLUENCING KNOWLEDGE AND ECONOMIC STATUS WITH MOTHER BREASTFEEDING - Imam Santoso; Bagus Rahmat Santoso; Rizki Amaliya Safitri (Universitas Sari Mulia, 2013)
Background: Exclusive breast feeding infants in early life is very beneficial, because breast milk is the best food it contains almost all the nutrients needed by the baby. However, mothers who deliver their baby exclusively breastfed until the age of 6months is still low.Method:The method used is an analytical survey with cross sectional design. With a population of all mothers with infants aged 6 – 12 month and samples in this study mothers who breastfeed their babies aged 6– 12 month as many as 64 people.Result :The results showed that many mother shave good knowledge as many as 31 people (48.43%), economic status, mothers were as many as 43 people(67.18%), mothers who breast feed as many as 33 people(51.56%), test analysis using Chi Square test with the knowledge that there is a influencing of breast-feeding p = 0,009α= 0,05. And there is a relationship of economic status mothers with breast feeding p = 0,009α= 0,05Conclusion :There is a influencing between knowledge and economic status of mothers with breast feeding in the work area.Keywords: Knowledge, economic status, breastfeeding.